2020
DOI: 10.3389/fcell.2020.593653
|View full text |Cite
|
Sign up to set email alerts
|

PECAM1 Combines With CXCR4 to Trigger Inflammatory Cell Infiltration and Pulpitis Progression Through Activating the NF-κB Signaling Pathway

Abstract: Pulpitis is a frequent bacterially driven inflammation featured with the local accumulation of inflammatory products in human dental pulps. A GEO dataset GSE16134 comprising data of inflamed dental pulp tissues was used for bioinformatics analyses. A protein-protein interaction (PPI) analysis suggested that chemokine receptor 4 (CXCR4) owned a high correlation with platelet endothelial cell adhesion molecule-1 (PECAM1). A rat model with pulpitis was established, and lipopolysaccharide (LPS)-induced human denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…It also triggers increased production of C5a—a chemotactic factor, taking part in recruiting inflammatory cells and pulp cells responsible for regeneration [ 114 ]. LPS-stimulated fibroblasts have increased mRNA and protein expressions of myocyte-enhancer factor 2 (MEF2C), platelet endothelial cell adhesion molecule-1 (PECAM1) and CXCR4 [ 115 ]. PECAM1 expression is positively correlated with B-cell signaling pathways, it also plays a role in angiogenesis [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also triggers increased production of C5a—a chemotactic factor, taking part in recruiting inflammatory cells and pulp cells responsible for regeneration [ 114 ]. LPS-stimulated fibroblasts have increased mRNA and protein expressions of myocyte-enhancer factor 2 (MEF2C), platelet endothelial cell adhesion molecule-1 (PECAM1) and CXCR4 [ 115 ]. PECAM1 expression is positively correlated with B-cell signaling pathways, it also plays a role in angiogenesis [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…LPS-stimulated fibroblasts have increased mRNA and protein expressions of myocyte-enhancer factor 2 (MEF2C), platelet endothelial cell adhesion molecule-1 (PECAM1) and CXCR4 [ 115 ]. PECAM1 expression is positively correlated with B-cell signaling pathways, it also plays a role in angiogenesis [ 115 ]. Binding PECAM1 to CXCR4 may intensify inflammation and apoptosis via NF-kB signaling pathway [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report by Cheng et al 89 suggested that PECAM1 was critical in the inflammatory response and apoptosis of hepatitis liver. Meanwhile, Liu et al found that PECAM1 could interact with CXCR4 in experimental pulpitis in mice, which lead to inflammatory response and increased apoptosis of human pulp fibroblasts by activating the NF-KB signaling pathway 90 . Wu found that PECAM-1 was found to be a negative regulator of monocyte derived osteoclast formation in PECAM-1 knockout mice 91 .…”
Section: Discussionmentioning
confidence: 99%
“…The key to sequestrating pro‐inflammatory factors is to inhibit the cascade of inflammatory pathway signalling 24 . Among these pathways, the NF‐kB pathway is a major regulator of inflammation due to its ability to cause transcription of numerous genes involved in the inflammatory response 25–27 . Therefore, inhibition of NF‐κB signalling in DPFs should be continued throughout the resolution process.…”
Section: Introductionmentioning
confidence: 99%